THE RELATIONSHIP BETWEEN WAITING TIME AND NURSE EMPATHY TOWARDS PATIENT SATISFACTION INTHE NEUROSURGERY POLYCLINIC OF ARIFIN ACHMAD REGIONAL HOSPITAL RIAU PROVINCE - Erianti, Susi (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2025)
Introduction: Patient satisfaction in the neurosurgery polyclinic is influenced by waiting time (standard < 60 minutes) and nurse empathy. Long waiting times can lead to patient anxiety and dissatisfaction. This study aimed to examine the relationship between waiting time and nurse empathy and their impact on patient satisfaction. Methods: This was a quantitative study with a descriptive correlational design using a cross-sectional approach. The study involved 89 respondents selected through consecutive sampling. Data were collected using questionnaires and analyzed using bivariate analysis with the Fisher’s Exact Test. Results: Of the respondents, 19 (23.3%) experienced short waiting times and 70 (78.7%) experienced long waiting times. Regarding nurse empathy, 3 respondents (3.4%) perceived it as moderate and 86 (96.6%) as high. For patient satisfaction, 67 respondents (75.3%) reported moderate satisfaction, while 22 (24.7%) reported high satisfaction. Fisher’s Exact Test showed no significant relationship between waiting time and patient satisfaction (p = 0.382), nor between nurse empathy and patient satisfaction (p = 0.150). Discussion: Although waiting time did not significantly affect patient satisfaction, reducing waiting time remains important for improving efficiency and comfort. This can be achieved through improved service flow, more efficient doctor scheduling, and increased room and facility capacity.